COVID-19: Return to sport or strenuous activity following infection - O'Connor, F. G.; Franzos, M. A. (UpToDate, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has had an unprecedented impact on physical activity and sport, affecting professional, elite, collegiate, tactical, occupational, and recreational athletes [1,2]. Sports participation was widely curtailed in 2020 to reduce viral spread, while tactical and occupational endeavors have required special precautions and modifications.